Incidental diagnosis of nonfunctional bladder paraganglioma: a case report and literature review - Xi Tu (BMC Urology, 2021)
Abstract Background Nonfunctional bladder paragangliomas is a rare urological disease. It may present clinical, radiology and pathological features similar to bladder cancer, Only scarce reports have been reported. Urologist must identify this generally benign neuroendocrine neoplasm to avoid misdiagnosis. Case presentation A 62-year-old female presented the outpatient department of our hospital with the symptoms of stomachache, frequent micturition, and urination pain for 20 days. Diagnosed with high blood pressure 1 year ago, administered Amlodipine besylate tablets 5 mg po qd occasionally, did not check blood pressure; denied any tumor observation in the family history. Color ultrasound of the urinary system showed a 38 mm × 34 mm hypoechoic mass on the right side of the bladder, CDFI: in the masses, blood supply was sufficient. Cystoscope showed bladder occupying lesion. Biopsy diagnosis: papillary polypoid cystitis was suspected as a malignant change (Fig. 3a). Then, the patient was admitted to our urological department. Further, computer tomography urography considered bladder cancer. Cystoscopy and biopsy failed to define the nature of the lesions in our outpatient department, which prompted a transurethral resection of the bladder tumor. histopathological and immunohistochemical results were diagnosed as bladder paragangliomas. For the reason, the tumor was removed by partial resection of the bladder. The postoperative recovery and follow-up were uneventful. Conclusions Nonfunctional bladder paragangliomas are occasionally found on imaging studies with the symptoms of urinary tract infection or/and intermittent painless hematuria. It may present clinical, radiology and pathological features similar to bladder cancer, so knowledge of this generally benign neuroendocrine neoplasm is of great importance to avoid misdiagnosis. It should be accompanied by the clinical and pathological characteristics of the patient and image changes. Partial resection of the bladder can effectively treat this disease.